Rational Improvement of Rice Yield and Cold Tolerance by Editing the Three Genes OsPIN5b, GS3, and OsMYB30 With the CRISPR–Cas9 System - Zeng, Yafei; Wen, Jianyu; Zhao, Weibo; Wang, Qiong; Huang, Wenchao (Frontiers in Plant Science, 2020)
ABSTRACT Significant increases in rice yield and stress resistance are constant demands for breeders. However, high yield and high stress resistance are often antagonistic to each other. Here, we report several new rice mutants with high yield and excellent cold tolerance that were generated by simultaneously editing three genes, OsPIN5b (a panicle length gene), GS3 (a grain size gene) and OsMYB30 (a cold tolerance gene) with the CRISPR-Cas9 (clustered regularly interspaced short palindromic repeats-associated protein 9) system. We edited two target sites of each gene with high efficiency: 53% for OsPIN5b-site1, 42% for OsPIN5b-site2, 66% for GS3-site1, 63% for GS3-site2, 63% for OsMYB30-site1, and 58% for OsMYB30-site2. Consequently, the ospin5b mutants, the gs3 mutants, and the osmyb30 mutants exhibited increased panicle length, enlarged grain size and increased cold tolerance, respectively. Then 9 transgenic lines of the ospin5b/gs3, 6 lines of ospin5b/osmyb30 and 6 lines of gs3/osmyb30 were also acquired, and their yield related traits and cold tolerance corresponded to the genes being edited. Additionally, we obtained eight ospin5b/gs3/osmyb30 triple mutants by editing all three genes simultaneously. Aside from the ospin5b/gs3/osmyb30-4 and ospin5b/gs3/osmyb30-25 mutants, the remaining six mutants had off-target events at the putative off-target site of OsMYB30-site1. The results also showed that the T2 generations of these two mutants exhibited higher yield and better cold tolerance compared with the wild type. Together, these results demonstrated that new and excellent rice varieties with improved yield and abiotic stress resistance can be generated through gene editing techniques and may be applied to rice breeding. Furthermore, our study proved that the comprehensive agronomic traits of rice can be improved with the CRISPR-Cas9 system. Keywords: OsPIN5b, GS3, OsMYB30, cold tolerance, panicle length, grain length, CRISPR/Cas9.